Sinergi Genre-Based Approach dan Cerpen Kontemporer dalam Meningkatkan Kompetensi Menulis Teks Tanggapan Siswa SMP - Elvandari, Dwi; Pratiwi, Winieke Dinar; Suntoko, Suntoko; Mauludani, Seli (Jurnal Bahasa dan Sastra, 2025)
The low level of students' response writing skills indicates a gap between the demands of the Merdeka Curriculum and the practice of Indonesian language learning in junior high schools. This study aims to test the effectiveness of the Genre-Based model assisted by selected short stories from Kompas 2021 in improving the response writing skills of seventh-grade students at public junior high schools in Jakarta. The method used was an experiment with a pretest-posttest control group design involving two classes, namely the experimental class and the control class, each consisting of 30 students. Data were obtained through a response text writing test assessed based on seven assessment indicators, then analyzed using normality tests, homogeneity tests, independent t-tests, and N-Gain. The results showed an increase in the average score of the experimental class from 58.70 to 84.57, while the control class increased from 57.43 to 68.87, with N-Gain scores of 63.28% (sufficiently effective category) and 25.39% (ineffective category), respectively. The t-test showed a significant difference between the two classes (Sig. < 0.05), so it can be concluded that the application of the Genre-Based model assisted by selected short stories from Kompas 2021 is effective in improving the response text writing skills of seventh-grade students at public junior high schools in Jakarta.